2016
DOI: 10.1016/j.sbspro.2015.12.081
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Towards Timber Frame Houses in China

Abstract: Timber framed architecture owns thousands of years' history in China.However, with the rapid industrialization and urbanization, timber frame houses have substantially deceased. In order to reduce the concentration of the greenhouses gas CO2 in the atmosphere and establish a low carbon society, the promotion of green building materials and energy saving buildings has been put in a prominent place by Chinese government. However, both of the number of timber frame houses and the potential of using timber, the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 2 publications
1
17
1
1
Order By: Relevance
“…For example, research by Annila, Lahdensivu, Suonketo, Pentti, and Vinha (2018) confirms this perception to be true; all load‐bearing building materials may be damaged by moisture and cause indoor air problems. Similar results were found regarding fire safety: while earlier quantitative studies (Gold & Rubik, 2009; Hu et al., 2016; Larasatie et al., 2018) indicate that residents are uncertain of the fire resistance of wood, our results show that the residents may also rationalize their feelings towards the topic:
It is a modern building, I think they have safety locks [in case of fire] … there will be fire alarms and everything. … I do not know if it is a risk per se … It will burn as any other building…—Interviewee 3, first round
…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…For example, research by Annila, Lahdensivu, Suonketo, Pentti, and Vinha (2018) confirms this perception to be true; all load‐bearing building materials may be damaged by moisture and cause indoor air problems. Similar results were found regarding fire safety: while earlier quantitative studies (Gold & Rubik, 2009; Hu et al., 2016; Larasatie et al., 2018) indicate that residents are uncertain of the fire resistance of wood, our results show that the residents may also rationalize their feelings towards the topic:
It is a modern building, I think they have safety locks [in case of fire] … there will be fire alarms and everything. … I do not know if it is a risk per se … It will burn as any other building…—Interviewee 3, first round
…”
Section: Resultssupporting
confidence: 87%
“…Previous studies on consumers and wood in urban housing have mainly shed light either on the acquisition processes, that is, purchase behaviour‐related questions (e.g., willingness to pay premiums, consumer attitudes) (e.g., Hu at al., 2016; Lähtinen et al., 2019; Luo, Mineo, Matsushita, & Kanzaki, 2018) or appreciations and devaluations related to wooden material (e.g., assigned meanings and perceptions) (e.g., Gold & Rubik, 2009; Karjalainen, 2002). These studies have found, for example, that residents appreciate the cosy and pleasant atmosphere of wooden multi‐storey buildings and the good indoor air quality of their apartments (Karjalainen, 2002).…”
Section: Wood As An Urban Housing Materials and Consumption Processes mentioning
confidence: 99%
See 2 more Smart Citations
“…This project set out with an understanding of the importance of commutation as means to promote consumer behavior. Previous research on consumer awareness in purchasing apartments in WMC [24][25][26][27][28][29] points to shortcomings in communication regarding climate effects.…”
Section: A Product-dominant Perspective-consumer Behaviormentioning
confidence: 99%